Malignant Melanoma in the Anterior Region of Maxillary Gingiva: A Rare Case Report - Twyana, Rajesh; yi, Zhang Hong; Wen, Jiang; Suwal, Saroj Kumar (Journal of Universal College of Medical Sciences, 2015)
Malignant melanoma is extremely rare neoplasm arising from uncontrolled growth of melanocytes, accounting for 0.5% of all oral malignancies. It has a great tendency to metastasize and locally invade tissues more readily than any other malignant tumor of the oral cavity. It present as the rare oral malignant condition, asymptomatic and poor prognosis. The necessity of a highly specialized treatment is factors that should be seriously considered by the involved health care provider. Herein, we report a rare and interesting case of oral malignant melanoma of the maxillary anterior gingiva, which was clinically and histo-pathologically diagnosed with a brief review of literature, has been discussed.